Tumor budding in invasive breast carcinoma: an emerging prognostic factor - Devashwar, Reetika; Mishra, P. S.; Venkatesan, S.; Bhatia, Jasvinder Kaur (International Journal of Research in Medical Sciences, 2024)
Background: Tumor budding refers to single or small cluster of tumor cells detached from the main tumor mass in histological sections. In colon cancer high tumor budding is associated with worse prognosis and correlates with metastatic lymph nodes. We studied tumor budding in modified radical mastectomy specimens to evaluate its utility as a prognostic factor by correlating high tumor budding score with known prognostic markers of breast cancer like axillary lymph nodal metastasis, clinical staging, tumor size, lymphovascular invasion, hormonal status and pathological grading. Aim was to evaluate tumor budding in invasive breast carcinoma and to describe clinical features and histopathological spectrum of Invasive Breast Carcinoma with/without lymph node metastasis on H&E slides. Secondly, to find association between grades of tumor budding and various clinical, gross, microscopic and immunohistochemical variables. Methods: The present study is a cross sectional study of 70 modified radical mastectomy specimens from June 2018 to Dec 2022. Along with tumor budding various prognostic parameters like hormonal markers, pathological grading and clinical grading were evaluated. Immunohistochemical marker Pancytokeratin was utilized for counting the tumor buds, wherever necessary. Statistical Analysis: Chi Square test was utilized to study significant differences between variables, p<0.05 was considered statistically significant. Results: A high tumor budding score (≥4/HPF) had significant association with axillary lymph node involvement and clinical staging. Conclusions: In our study we detected the association of high tumor budding, PTB in invasive breast carcinoma with axillary lymph node involvement and clinical staging. Hence our results highlight the importance of tumor budding as a prognostic factor and submit that this histological feature could be included in diagnostic protocols just as in carcinoma of the colon.